Unveiling a family of spiro-β-lactams with anti-HIV and antiplasmodial activity via phosphine-catalyzed [3+2] annulation of 6-alkylidene-penicillanates and allenoates - Alves, Américo J. S.; Alves, Nuno G.; Bártolo, Inês; Fontinha, Diana; Caetano, Soraia; Prudêncio, Miguel; Taveira, Nuno; Pinho e Melo, Teresa M. V. D. (Frontiers in Chemistry, 2022)
The molecular architecture of spirocyclic compounds has been widely explored within the medicinal chemistry field to obtain new compounds with singular three-dimensional pharmacophoric features and improved bioactivity. Herein, the synthesis of sixty-eight new spirocyclopentenyl-β-lactams is described, resulting from rational drug design and structural modulation of a highly promising lead compound BSS-730A, previously identified as having dual antimicrobial activity associated with a novel mechanism of action. Among this diverse library of new compounds, twenty-two were identified as active against HIV-1, with eight displaying an IC50 lower than 50 nM. These eight compounds also showed nanomolar activity against HIV-2 and six of them displayed micromolar anti-plasmodial activity against both the hepatic and the blood stages of infection by malaria parasites, in agreement with the lead molecule’s bioactivity profile. The spirocyclopentenyl-β-lactams screened also showed low cytotoxicity against TZM-bl and Huh7 human cell lines. Overall, a family of new spirocyclopentenylpenicillanates with potent activity against HIV and/or Plasmodium was identified. The present structure-activity relationship open avenues for further development of spirocyclopentenyl-β-lactams as multivalent, highly active broad spectrum antimicrobial agents.